MAKNA MITOS CERITA BURUNG ENGGANG DI KALIMANTAN TIMUR - Hanum, Irma Surayya; Dahlan, Dahri (Fakultas Ilmu Budaya, Universitas Mulawarman, 2018)
This research will analyze the folklore of East Borneo in the form of myth about the hornbill descended down by Dayak Kenyah people associated with its relevance to the development of nation character. The theory used is the theory of 'layers of social reality'. The theory will reveal five layers of meaning contained in a system or symbol contained in culture and tradition. Starting from the meaning of layers of empirical meaning, to the meaning of the layer of world view at the level of ideas that store local wisdom. These findings will be formulated in the form of recommendations to specific parties, for example for the preparation of curriculum, especially local content subjects at the school level, and or for East Kalimantan Literature courses at the university level.